THE IMPORTANCE OF KNOWLEDGE ABOUT HEALTH PROTOCOLS FOR THE PREVENTION OF COVID-19 TRANSMISSION IN NON-MEDICAL STUDENTS OF SURABAYA, INDONESIA - Nadia Mardiana Hudan; Grawira Drana Putra Respati; Hamzah Rafly Rahman; Danti Nur Indiastuti; Ekiyanti, Khisma (Journal of Community Medicine and Public Health Research, 2022)
Lack of public compliance with the implementation of health protocol activities in daily life has resulted in increased cases of Covid-19 in Indonesia, so the government issued the latest policy regarding the health protocol, namely 6M, which consists of wearing masks, maintaining hand hygiene, maintaining distance, reducing mobility, staying away from crowds, and avoid eating together. This study aims to educate and make the public more aware of the importance of health protocols during the Covid-19 pandemic. This research used total sampling method. The target of the counseling was non-medical students in Surabaya who took part in Covid-19 educational counseling by filling out complete pre-test and post-test questions. The results obtained were an increase in the average score (17.26 points) on tests filled before and after the educational presentation of health protocols with a value of p<0.001 (p<0.05), and 34 of them showed higher post-test scores. From the data that obtained from 92 samples, there was an increase and significant difference in knowledge about 6M health protocols after an online educational presentation given to non-medical students in Surabaya as evidenced by the increase in average score between pre-test and post-test.